Growing taller unequally? Adult height and socioeconomic status in Spain (Cohorts 1940-1994) - Begoña Candela-Martínez; Antonio D. Cámara; Diana López-Falcón; José M. Martínez-Carrión (Elsevier, 2022)
Socioeconomic inequalities and their evolution in different historical contexts have been widely studied. However, some of their dimensions remain relatively unexplored, such as the role played by socioeconomic status in the trajectory of biological living standards, especially net nutritional status. The main objective of this article is to analyze whether the power of socioeconomic status (SES) to explain differences in the biological dimensions of human well-being (in this case, adult height, a reliable metric for health and nutritional status) has increased or diminished over time. Educational attainment and occupational category have been used as two different proxies for the SES of Spanish men and women born between 1940 and 1994, thus covering a historical period in Spain characterized by remarkable socioeconomic development and a marked increase in mean adult height. Our data is drawn from nine waves of the Spanish National Health Survey and the Spanish sample of two waves of the European Health Interview Survey (ENSE) for the period 1987 to 2017 (N = 73,699 citizens aged 23-47). A multivariate regression analysis has been conducted, showing that, as a whole, height differentials by educational attainment have diminished over time, whereas differences by occupational category of household heads have largely persisted. These results indicate the need for further qualification when describing the process of convergence in biological well-being indicators across social groups. For instance, the progressive enrollment of a greater proportion of the population into higher educational levels may lead us to underestimate the real differences between socioeconomic groups, while other proxies of SES still point to the persistence of such differences.